Health-related quality of life and its associated factors among Chinese seasonal retired migrants in Hainan - Chen, Sikun; Li, Tianchang; Wang, Lingjun; Wang, Shigong; Ouyang, Lin; Wang, Jiwei; Hu, Dayi; Yu, Jinming (PeerJ, 2024)
Background Seasonal retired migrants are mainly retired or semiretired people who migrate to warmer areas during the winter and then return to their original homes in the following year. Despite its increasing popularity, the evidence concerning the health status of Chinese seasonal retired migrants is controversial. Although some studies have shown that seasonal retired migrants have better health status, other studies note that migrants are driven involuntarily by health concerns and that their mental health suffers during migration. The objective of this study was to provide quantified evidence on the health-related quality of life (HRQoL) of seasonal retired migrants in China and to identify potential factors associated with HRQoL. Methods This was a community-based cross-sectional study of seasonal retired migrants who lived in Wuzhishan, Hainan during the winter. The Chinese version of the EuroQol 5-Dimension 5-Level (EQ-5D-5L) was used to assess participants’ HRQoL. Data on demographic and behavioral characteristics, body mass index, and the presence of chronic diseases were collected using a self-administered survey. Logistic regressions were used to explore the factors associated with responses in each dimension of the EQ-5D-5L descriptive system, and a multiple linear regression model was used to explore the factors associated with EuroQol visual analogue scale (EQ-VAS) scores. Results A total of 992 participants (female: 56.5%) were enrolled in the current study, with a mean age of 67.87 ± 6.98 years. Most participants reported problems in the pain/discomfort dimension (16.7%), followed by the anxiety/depression dimension (8.3%). Few participants reported problems in the first three dimensions of the EQ-5D-5L: mobility (5.4%), usual activities (2.0%), and self-care (1.2%). The median EQ-VAS score was 84 (interquartile range: 80–89). The regression results indicated that poor sleep quality, the presence of chronic diseases, and low-level physical activity were important factors that were negatively associated with multiple dimensions of the EQ-5D-5L. In addition, the EQ-VAS score was negatively associated with age, the presence of chronic diseases, poor sleep quality, and low-level physical activity. Conclusion This study revealed that Chinese seasonal retired migrants have high HRQoL. In addition, this study revealed that sleep quality and physical activity are correlated with multiple dimensions of the EQ-5D-5L descriptive system and EQ-VAS. Therefore, lifestyle interventions related to sleep quality and physical activity are essential for improving HRQoL among Chinese seasonal retired migrants.
Keywords: Health-related quality of life; EQ-5D; Seasonal retired migrants; Seasonal migration